2007
DOI: 10.1016/j.neuroscience.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

L1 cell adhesion molecule is not required for small-diameter primary afferent sprouting after deafferentation

Abstract: L1 is a cell adhesion molecule associated with axonal outgrowth and fasciculation during spinal cord development and may reiterate its developmental role in adults following injury; L1 is upregulated on certain sprouting and regenerating axons in adults, but it is unclear if L1 expression is necessary for, or contributes to, regrowth of axons. This study asks if L1 is required for small-diameter primary afferents to sprout by conducting unilateral dorsal rhizotomies (6 segments; T10-L2) on both wildtype and L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
2
6
3
Order By: Relevance
“…In contrast to some earlier reports demonstrating IB4-binding to astrocytes and microglial cells (Streit, 1990; Villeda et al, 2006; Runyan et al, 2007), we have never seen IB4-binding on glial cells in the present study (Supporting Information Figure 6). Despite the strong immunostaining and the substantial spatial overlap between the investigated profiles, the co-localization between axon terminals labeled with IB4-binding and puncta immunoreactive for DGLα or NAPE-PLD was very low.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to some earlier reports demonstrating IB4-binding to astrocytes and microglial cells (Streit, 1990; Villeda et al, 2006; Runyan et al, 2007), we have never seen IB4-binding on glial cells in the present study (Supporting Information Figure 6). Despite the strong immunostaining and the substantial spatial overlap between the investigated profiles, the co-localization between axon terminals labeled with IB4-binding and puncta immunoreactive for DGLα or NAPE-PLD was very low.…”
Section: Resultscontrasting
confidence: 99%
“…Despite evidence that favored a contact-mediated role for L1 in OEG-enhanced regeneration, OEG stimulated axonal outgrowth regardless of the presence or absence of L1 in our assay. Our findings are consistent with those using the L1 mutant mouse model that report L1 expression is not essential for DRG sprouting following unilateral deafferentation (Runyan et al, 2007) or growth of the corticospinal tract into a contusion injury (Jakeman et al, 2006). These results suggest that other cell adhesion molecules or extracellular matrix proteins expressed by OEG, such as PSA-NCAM, must participate in contact-mediated growth promotion.…”
Section: Discussionsupporting
confidence: 91%
“…L1 is down-regulated on most axons during postnatal development (Akopians et al, 2003), but is maintained on adult small-diameter DRG nociceptors (Haney et al, 1999; Runyan et al, 2005; Runyan et al, 2007) and on the Schwann cells that ensheath these unmyelinated axons (Haney et al, 1999). Using L1-deficient mice Haney et al (1999) found that Schwann cells did not maintain ensheathment of DRG axons, due to the loss of axonal L1.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this, we saw significantly increased CGRP + fiber sprouting in the lumbar dorsal horn after injury in WT mice when compared with uninjured WT controls. L1 and CGRP are co-expressed in these afferents (Runyan et al, 2005), and the influence of L1 as a growth molecule on CGRP+ fiber sprouting has been shown and discussed previously (Chaudhry et al, 2006; Runyan et al, 2007; Deumens et al, 2007; Yamanaka et al, 2007). Notably, L1 has also been shown to contribute to synapse formation and stabilization (Godenschwege et al, 2006; Triana-Baltzer et al, 2008) as well as the survival of small-diameter unmyelinated afferent axons in the periphery (Haney et al, 1999).…”
Section: Discussionmentioning
confidence: 85%